Effect Of Compound Formulation On The Production And Properties Of Epoxidised Natural Rubber (Enr-25) Foams. - Ariff, Z M; Rahim, N A A; L, C Low (2008)

(untitled)
In this study, Epoxidized Natural Rubber (ENR-25) formulations are compounded and tested to obtain a stable expandable rubber foam as well as to determine the foam cell physical morphology and its mechanical properties. The experiment was carried out by employing different ratio of rubber blend between ENR-25 and natural rubber (SMR-L), different amount of blowing agent which is Sodium Bicarbonate and different ratio of accelerator between Tetramethylthiuram-disulfenamide (TMTD) and N-cyclohexyl-2-benzotiazolsulfenamide (CBS).